Characterization of candidate proteins involved in calreticulin-dependent invasion using breast cancer tissue biopsies - Noudehi, Zahra Yekta Moghaddam (2012)
Breast cancer is one of the most common malignancies among women and accounts for more than one-fifth of all female cancer deaths. Invasive ductal carcinoma is the largest sub-type of invasive breast cancers. Tumor cells can alter their ability to adhere to both surrounding cells and the extracellular matrix during invasion. The delineation of the molecular networks and pathways that affect invasion has been a central target in biomedical research. A large number of proteins have been implicated in breast cancer invasion and one important protein is calreticulin (CRT). CRT is a high-capacity calcium-binding protein found in the endoplasmic reticulum (ER) lumen and has been implicated in a variety of functions outside of the ER, including cell adhesion and integrin-dependent calcium signaling. CRT has been found to be over-expressed in cancers including breast cancer. It is postulated to have an important role in the development and progression of cancers through the enhancement of cell motility and anoikis resistance. It is hypothesised that the effect of CRT over-expression on cell adhesion is due to the effect of CRT-dependent cellular signaling pathways. There are many proteins that CRT is linked to and hypothesised to contribute to the conferment, maintenance and increment of the invasive potential of breast cancer cells. Previous studies have shown that there correlations between CRT over-expression and some of the proteins involved in cancer cell invasion exist. The protein candidates investigated in this study are found to be implicated with a cancer invasive phenotype and potentially CRT-dependent. Hence the main objective of this study was to determine the expression and localization patterns of MUC1, TSP-1, CTTN, E-cadherin, and HER-2/neu in breast cancer tissues and corresponding non-malignant tissues. In this study, immunohistochemistry (IHC) analysis was employed to evaluate the expression patterns of the selected proteins in 46 formalin-fixed paraffin-embedded breast cancer and non-malignant tissues. Semi-quantitative immunohistochemical analyses demonstrated differing degrees of differential expression patterns of MUC1, TSP-1, CTTN, E-cadherin and HER-2/neu proteins in breast cancer tissues. MUC1 protein was over-expressed in the malignant tissues as compared to non-malignant tissues (p<0.05), and also showed positive correlation with CRT expression. TSP-1 over-expression was not significant between non-malignant and malignant tissues. Nevertheless TSP-1 was over-expressed in a subset of stage 4 and grade 3 tumors. There was a correlation of expression between TSP-1 and CRT. CTTN protein showed a significant decrease in expression in malignant tissues as compared to non-malignant tissues (p<0.05). Comparison of CTTN and CRT expression also yielded no correlation in expression patterns. E-cadherin expression was decreased in stage 2 tumors but when compared between malignant and non-malignant tissues, there was no significant loss of expression. However, there was an inverse correlation between E-cadherin and CRT expression patterns. HER-2/neu analyses showed significant over-expression in malignant lesions as compared to non-malignant (p<0.05), but there was direct correlation between HER-2/neu and CRT expression patterns. In conclusion, this study identified a positive association between CRT and HER-2/neu, MUC1, and TSP-1 and a negative association between CRT and E-cadherin in breast cancer. This body of work will form the basis for future validation studies of expression patterns as well as the molecular dissection of CRT-dependent pathways that are linked to invasive breast cancers. HER-2/neu and MUC1 proteins over-expression can potentially be used as molecular markers for early detection of breast cancer.